2012
DOI: 10.1007/s00436-011-2780-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel cathepsin B-like cysteine proteinase from Angiostrongylus cantonensis

Abstract: Cysteine protease plays a key role in host-parasite interactions. In this study, we identified a novel gene encoding a cathepsin B-like cysteine protease (AcCBL1) from the cDNA library of Angiostrongysus cantonensis fourth-stage larvae (L4) and characterized its biological role in the parasite. Sequence and phylogeny analysis showed that AcCBL1 is related to other cathepsin B family members with the conserved catalytic triad (Cys, His, Asn) and diagnostic occluding loop. In addition, the sequence contains a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Cysteine protease is a candidate diagnostic antigen with good specificity for some helminth infections, including Angiostrongylus cantonensis [ 33 ], Necator americanus [ 39 ], Toxocara canis [ 15 ], Paragonimus westermani [ 14 ], Schistosoma japonicum [ 40 ], Clonorchis sinensis [ 41 ], Taenia solium [ 42 ], and S . erinaceieuropaei [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteine protease is a candidate diagnostic antigen with good specificity for some helminth infections, including Angiostrongylus cantonensis [ 33 ], Necator americanus [ 39 ], Toxocara canis [ 15 ], Paragonimus westermani [ 14 ], Schistosoma japonicum [ 40 ], Clonorchis sinensis [ 41 ], Taenia solium [ 42 ], and S . erinaceieuropaei [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity of rSeCP was assayed by substrate gel electrophoresis with a 12% SDS–PAGE gel copolymerized with 0.1% gelatin as the substrate, as previously reported [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are many genes of A. cantonensis having been cloned and analyzed. They are cysteine protease inhibitor , matrix metalloproteinase (Sun et al 2012), cathepsin B-like cysteine proteinase (Cheng et al 2012), protein disulfide isomerases , novel gene encoding 16 kDa protein (Li et al 2012a), cathepsin B (Han et al 2011), galectin-10 (Liu et al 2013, etc. These work establish the foundation for researching the vaccine against A. cantonensis and searching drug target of angiostrongylsis.…”
Section: Molecular Biology Of a Cantonensismentioning
confidence: 98%
“…One year later, sequence analysis of the gene encoding the identified cathepsin showed that it contains a specific hemoglobinase motif to hydrolyze several host proteins including hemoglobin and human IgG. Using WB, cathepsin B was found in E/S from 4 th stage larvae, and the investigators suggested its role in parasite nutrition [177] . In the same year, Brazilian investigators immunoblot A. cantonensis E/S against pooled sera from patients with angiostrongyliasis and healthy controls.…”
Section: • Angiostrongylus Cantonensis: Angiostrongyliasismentioning
confidence: 99%